Combination of elacridar with imatinib modulates resistance associated with drug efflux transporters in chronic myeloid leukemia - Alves, Raquel (2022)
Multidrug resistance (MDR) development has emerged as a complication that compromises the success of several chemotherapeutic agents. In chronic myeloid leukemia (CML), imatinib resistance has been associated with changes in BCR-ABL1 and intracellular drug concentration, controlled by SLC and ABC transporters. We evaluate the therapeutic potential of a P-glycoprotein and BCRP inhibitor, elacridar, in sensitive (K562 and LAMA-84) and imatinib-resistant (K562-RC and K562-RD) CML cell lines as monotherapy and combined with imatinib. Cell viability was analyzed by resazurin assay. Drug transporter activity, cell death, cell proliferation rate, and cell cycle distribution were analyzed by flow cytometry. Both resistant models presented an increased activity of BCRP and P-gP compared to K562 cells. Elacridar as monotherapy did not reach IC50 in any CML models but activated apoptosis without cytostatic effect. Nevertheless, the association of elacridar (250 nM) with imatinib overcomes resistance, re-sensitizing K562-RC and K562-RD cells with five and ten times lower imatinib concentrations, respectively. Drug combination induced apoptosis with increased cleaved-caspases-3, cleaved-PARP and DNA damage, reduced cell proliferation rate, and arrested CML cells in the S phase. These data suggest that elacridar combined with imatinib might represent a new therapeutic option for overcoming TKI resistance involving efflux transporters. View Full-Text